Collaborative Governance dalam Menciptakan Branding Kota Surakarta Sebagai Kota Festival - Robi Suwarna (Department of Public Administration, Muhammadiyah University of Makassar, 2023)
Festival activities are carried out as part of tourism promotion to market Surakarta City so that it can compete with other cities in the world in attracting investment, attracting tourists, and so on. It is necessary to identify the urban development plans carried out by the City of Surakarta, describe the roles of various actors from various sectors in the successful implementation of festival activities in the City of Surakarta, and explain the governance shape used in the City of Surakarta. The method used is descriptive and explanatory research with a qualitative approach to describe the development plans for the City of Surakarta and describe the integrative framework in Collaborative Governance that occurs in organising festival activities. The result of this research is the development plan for Surakarta City is to carry out city branding as a Festival City with a specific theme, namely its culture and the success of its implementation is the result of the collaboration of various actors from various sectors with their respective roles which an integrative framework model for Collaborative Governance can describe. This study concluded that Collaborative Governance is a governance shape carried out in Surakarta's city development planning. Collaborative Governance is considered a very good thing that impacts the economic and social community and cultural preservation.